Epidemics in the news: health and hygiene in the press in periods of crisis - Almeida, M. (Public Understanding of Science, 2013)
How did scientific knowledge reach the public? Using the press and keeping in mind the population’s limited access to written material, the purpose is to establish how the latest scientific news were divulged to unspecialised audiences. In times of sanitary crisis in Oporto, such as the cholera morbus epidemic of 1854-56, the bubonic plague in 1899 and the 1918 influenza pandemic, newspapers are important sources to access the information and advice given to the public. A database of 6.700 articles, medical reports and advertisements published in daily newspapers reveals the state of the art of medical science. It also reveals the importance given by health authorities and journalists to the publication of recent discoveries and adequate hygiene procedures to prevent the spread of the epidemics. This is a subject that contributes to the debates on the dissemination of science and on the place that Portugal occupied in the international scientific community.